Divulging diazotrophic bacterial community structure in Kuwait desert ecosystems and their N2-fixation potential. - M K Suleiman; A M Quoreshi; N R Bhat; A J Manuvel; M T Sivadasan (PLoS ONE)
Kuwait is a semi-arid region with soils that are relatively nitrogen-poor. Thus, biological nitrogen fixation is an important natural process in which N2-fixing bacteria (diazotrophs) convert atmospheric nitrogen into plant-usable forms such as ammonium and nitrate. Currently, there is limited information on free-living and root-associated nitrogen-fixing bacteria and their potential to fix nitrogen and aid natural plant communities in the Kuwait desert. In this study, free living N2-fixing diazotrophs were enriched and isolated from the rhizosphere soil associated with three native keystone plant species; Rhanterium epapposum, Farsetia aegyptia, and Haloxylon salicornicum. Root-associated bacteria were isolated from the root nodules of Vachellia pachyceras. The result showed that the strains were clustered in five groups represented by class: γ-proteobacteria, and α-proteobacteria; phyla: Actinobacteria being the most dominant, followed by phyla: Firmicutes, and class: β-proteobacteria. This study initially identified 50 nitrogen-fixers by16S rRNA gene sequencing, of which 78% were confirmed to be nitrogen-fixers using the acetylene reduction assay. Among the nitrogen fixers identified, the genus Rhizobium was predominant in the rhizosphere soil of R. epapposum and H. salicornicum, whereas Pseudomonas was predominant in the rhizosphere soil of F. aegyptia, The species Agrobacterium tumefaciens was mainly found to be dominant among the root nodules of V. pachyceras and followed by Cellulomonas, Bacillus, and Pseudomonas genera as root-associated bacteria. The variety of diazotrophs revealed in this study, signifying the enormous importance of free-living and root-associated bacteria in extreme conditions and suggesting potential ecological importance of diazotrophs in arid ecosystem. To our knowledge, this study is the first to use culture-based isolation, molecular identification, and evaluation of N2-fixing ability to detail diazotroph diversity in Kuwaiti desert soils.